Potential airway compromise secondary to impacted Wharton's duct calculus: a noteworthy phenomenon. Issue 7 (8th July 2015) - Van, M; Gohil, R; Gardiner, Q
Abstract Objectives: This case report describes a patient who suffered an acute, severe complication of unilateral submandibular sialolithiasis, the disease process and management of these patients. Case report: A 70-year-old woman was under investigation for a recurrent, painful right submandibular swelling and subsequently presented with an acute exacerbation. She exhibited symptoms of acute submandibular sialadenitis, and also reported breathing difficulty and a change in voice quality. Computed tomography imaging showed that this was caused by a submandibular gland duct sialolith, with inflammation extending to the ipsilateral supraglottis. She was treated medically and the stone was removed when the inflammation had stabilised. Conclusion: This case highlights the need to thoroughly assess patients with neck swellings, especially when symptoms are atypical, to avoid life-threatening complications.